2008
DOI: 10.1021/jp711985f
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and Surface Switching in Mn−Fe-Based Prussian Blue Analogues

Abstract: Many Prussian Blue Analogues are known to show a thermally induced phase transition close to room temperature and a reversible, photo-induced phase transition at low temperatures. This work reports on magnetic measurements, X-ray photoemission and Raman spectroscopy on a particular class of these molecular heterobimetallic systems, specifically on Rb0.97Mn[Fe(CN)6]0.98·1.03H2O, Rb0.81Mn[Fe(CN)6]0.95·1.24H2O and Rb0.70Cu0.22Mn0.78[Fe(CN)6]0.86·2.05H2O, to investigate these transition phenomena both in the bulk … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Such structural features modulate the charge density on the metal linked at the N end, which is sensed through the core electrons binding energy. With few exceptions,, the main reports on the applications of XPS in that sense dated from several decades ago, when some of the mentioned structural features were unknown or received little attention. In addition, in the last two decades, the possibility to have XPS data recorded under high‐resolution condition has received large improvement, mainly due to the availability of more versatile instruments and advanced models and software for data processing.…”
Section: Introductionmentioning
confidence: 99%
“…Such structural features modulate the charge density on the metal linked at the N end, which is sensed through the core electrons binding energy. With few exceptions,, the main reports on the applications of XPS in that sense dated from several decades ago, when some of the mentioned structural features were unknown or received little attention. In addition, in the last two decades, the possibility to have XPS data recorded under high‐resolution condition has received large improvement, mainly due to the availability of more versatile instruments and advanced models and software for data processing.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 2088 and 2149 cm −1 are assigned to symmetry‐spit normal modes of Fe II ‐CN‐Fe III , which are observed for PB, but not for MWCNT‐PB in 31b. 32 The FTIR and Raman spectra both show the absence of the ν(CN) band of PB in MWCNTs‐PB in , which again validates the successful removal of outer‐surface PB.…”
Section: Resultsmentioning
confidence: 61%
“…and Fe 3+ -CN-M 3+ (M = transition metal) have been reported to typically correspond to the ranges of 2065-2110, 2090-2140, 2146-2185 and 2180-2210 cm −1 in the Raman and infrared spectrum, respectively [10,11]. Therefore, the peaks at 2170 and 2234 cm −1 in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…2b can be assigned to LTP, since a previous report by Cobo et al [12] clearly assigned two sharp peaks at 2096 and 2114 cm −1 to LTP. Furthermore, Vertelman et al [10] and Lummen et al [11] have observed several broadened peaks at 2086-2130 cm −1 in the Raman spectra and assigned them to LTP. Based on these studies, we attributed the peaks at 2096 and 2137 cm −1 in Fig.…”
Section: Resultsmentioning
confidence: 99%